Probabilistic approach to the choice of options for placing an order in order to minimize the risks of spending financial resources in making management decisions - Parkhomenko, Pavlo (Social Development and Security, 2020)
One of the problems that arises in the daily practice of management – fund managers in making management decisions, namely – finding the most economical option for placing an order between several potential contractors to save budget funds and minimize possible risks of exceeding customer costs.An approach is proposed using the statistical method of quantitative risk analysis based on the definition of two indicators: the probability of obtaining savings and the risk of not obtaining the expected savings. An example of using the proposed approach for two options for placing an order between three potential contractors. The mechanism of summary of calculations in the final table acceptable for the analysis and acceptance of the final decision in a management instance is offered.It is noted that this approach can be applied in the presence of more than two alternative options for the distribution of orders and for more than three potential contractors.